Whole-Transcriptome Analysis of LncRNAs Mediated ceRNA Regulation in Granulosa Cells Isolated From Healthy and Atresia Follicles of Chinese Buffalo - Pan, Yu; Yang, Sufang; Cheng, Juanru; Lv, Qiao; Xing, Qinghua; Zhang, Ruimen; Liang, Jingyuan; Shi, Deshun; Deng, Yanfei (Frontiers in Veterinary Science, 2021)
Granulosa cells (GCs) are the main supporting cells in follicles and play an important role in the regulation of oocyte maturation and follicular atresia. Accumulating evidence indicates that noncoding RNAs participate in regulation of the physiological function of GCs. However, whole-transcriptome analysis for GCs of buffalo has yet to be reported. In this study, healthy follicles (HFs) and atretic follicles (AFs) were defined according to the apoptosis rate of GCs and the hormone level in follicular fluid. GCs were collected from HFs and AFs (n=15, 5mm